Indonesian Curcuma Competition in the World Market: Insight from Demand System Analysis - Yafi, Muhammad Ali (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2025)
Curcuma is frequently employed as an appetite enhancer and for medicinal purposes. In addition to being consumed domestically, Indonesian curcuma is also exported to the global market. This research identifies the manner in which Indonesian curcuma competes in the worldwide market, taking into account the fact that it also competes with curcuma from various other countries. The market position of Indonesian curcuma is identified using the Almost Ideal Demand System (AIDS) method. The comparator countries selected for this study are five curcuma exporters, namely India, the Netherlands, Germany, Spain, and the USA. The analysis utilised time series data from January 2013 to December 2022, and the identification results of this study indicate that Indonesian curcuma is a normal good with elastic and responsive properties to the global demand for curcuma. Furthermore, it is observed that Indonesian curcuma substitutes or replaces Indian curcuma. Conversely, Dutch, German, Spanish, and USA curcuma exhibit a complementary relationship with Indonesian curcuma. To enhance the competitiveness of Indonesian curcuma in the global market, it is imperative to augment the volume and quality of exports, with a particular focus on standardisation and enhancing the added value through processing. This strategic approach is expected to not only ensure price competitiveness with other exporters but also to expand the share of Indonesian curcuma exports in the global market.